BRAND EQUITY ANALYSIS OF DECISIONS TO PURCHASE NOBRANDEDON DENIM PRODUCTS - Indika, Deru R; Adhari, Farras Ilham (Jurnal Ekonomi dan Bisnis, 2018)
This study aims to analyze whether brand equity can influence consumer purchasing decisions. The research used is descriptive through interviews and surveys with the object of the research being Nobrandendon, a company of denim fashion products that is located in the city of Bandung. The results of the questionnaire were collected from consumers who came to Nobrandendon store during February-May 2018. From the results of the study found that good brand equity, especially perceived quality, will influence consumers in deciding purchases, especially at the information search stage